2015
DOI: 10.1007/s11011-015-9736-3
|View full text |Cite
|
Sign up to set email alerts
|

Idalopirdine – a small molecule antagonist of 5-HT6 with therapeutic potential against obesity

Abstract: 5HT6 receptor antagonists offer the potential for safe and effective drugs against obesity, because they can reduce weight without causing serious side effects in the cardiovascular system. Also, their anorexic effect is associated with reduced food intake via an enhancement of satiety. In the present study we investigated the anorexic effect of idalopirdine (LuAE58054) in a model of obesity induced by high-fat diet. To induce obesity in rats, the animals were treated with feed with a fat content of 40 %. Body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…The spontaneous activity of the mice was measured on the fourteenth day of the treatment with a special, innovative RFID-system (Radio-frequency identification system) – TraffiCage (TSE-Systems, Germany). The test was conducted according to the method described in the literature (Dudek et al 2015a ; Dudek et al 2015b ; Dudek et al 2016 ). The animals had the transmitter (RFID) subcutaneously implanted, which tracked the time they spent in different areas of the cage.…”
Section: Methodsmentioning
confidence: 99%
“…The spontaneous activity of the mice was measured on the fourteenth day of the treatment with a special, innovative RFID-system (Radio-frequency identification system) – TraffiCage (TSE-Systems, Germany). The test was conducted according to the method described in the literature (Dudek et al 2015a ; Dudek et al 2015b ; Dudek et al 2016 ). The animals had the transmitter (RFID) subcutaneously implanted, which tracked the time they spent in different areas of the cage.…”
Section: Methodsmentioning
confidence: 99%
“…The standard diet contained 100 g of feed-280 kcal. The spontaneous activity of rats was measured on the 1st, 14th and 20th day of the treatment with a special RFID-system-TraffiCage (TSE-Systems, Germany) [45,46]. The animals were subcutaneously implanted with transmitter identification (RFID), which enabled the presence and time spent in different areas of the cage to be counted; the data were then grouped in a special computer program.…”
Section: The Effect Of Kmp-10 On Food and Water Intake By Non-obese Rmentioning
confidence: 99%
“…Thus, with a multitude of interactions not fully elucidated, preclinical studies on both 5-HT 6 agonists and 5-HT 6 antagonists have shown efficacy against depression, anxiety, and cognitive impairment (1). In addition, 5-HT 6 antagonists have shown promise in the treatment of obesity (7), major depressive disorder (8), age-related cognitive decline (9), and schizophrenia (10). Currently available antidepressants and antipsychotics have also been shown to have a strong affinity for the 5-HT 6 receptor (11,12), adding speculation that these clinical effects might, at least in part, be mediated through this receptor.…”
mentioning
confidence: 99%